The Influence Of Product Innovation, Marketing Innovation And Process Innovation On Performance Of Food Business Msmes In Lengkong District, Bandung City, West Java - Ahnaf, Muhammad Farrel; Trianasari, Nurvita (eProceedings of Management, 2025)
The contribution of MSMEs to the Indonesian economy is significant. Equalising the economic status of small persons is one of the duties carried out by MSMEs. In this case, MSMEs can be located in various areas, even in remote areas, so that people do not need to go far to the city to find a decent living. One of the MSMEs developing in Bandung is Food MSMEs in Lengkong. Finding out how product innovation, marketing innovation, and process innovation affect the performance of MSMEs is the main goal of this study. Keywords: product innovation, marketing innovation, process innovation, MSMEs performance.